Effects of low-pH treatment on cAMP second messenger system regulated by different opioid agonists - Liu Jing-gen; Gong Ze-hui; Qin Bo-yi (Acta Pharmacologica Sinica, 2016)
AIM: To study the mechanism of opioid agonists in regulation of cAMP second messenger system. METHODS: Low-pH treatment was used to deplete the stimulatory G protein (Gs) function. The effects of some opiates on adenylate cyclase were compared between control and low-pH treatment membranes. RESULTS: In contrast to dehydroetorphine (DHE), etorphine (Eto), morphine (Mor) and methadone (Met) substantially increased the inhibitory effects on adenylate cyclase in membranes prepared from naive and chronic Mor- or Met-treated NG108-15 cells by low-pH treatment. In contrast to Mor, DHE and Eto did not result in significant decrease in the inhibitory effects on adenylate cyclase in membranes from the cells treated chronically with DHE or Eto. Marked rebound of adenylate cyclase was also not observed in membranes from chronic DHE or Eto-treated cells when precipitated with naloxone. Low-pH treatment eliminated naloxone-induced rebound of adenylate cyclase in chronic Mor-treated cells. CONCLUSION: The difference in opiate-induced functional adaptive alteration of Gs is at least one biochemical mechanism of developing opiate tolerance and dependence.